Expert Political Judgment : How Good Is It? How Can We Know? - Tetlock, Philip E. (Philip Eyrikson), 1954- (Book collections on Project MUSE., 2005)
The intelligence failures surrounding the invasion of Iraq dramatically illustrate the necessity of developing standards for evaluating expert opinion. This book fills that need. Here, Philip E. Tetlock explores what constitutes good judgment in predicting future events, and looks at why experts are often wrong in their forecasts. Tetlock first discusses arguments about whether the world is too complex for people to find the tools to understand political phenomena, let alone predict the future.